Inequality among Children and Elderly in Ten Modern Nations: The United States in an International Context - Coder, John; Rainwater, Lee; Smeeding, Timothy M. (American Economic Review, 1989)
All modern countries are concerned about poverty and inequality amid their populations in general, and with that among their major dependent groups: children and elderly, in particular. The purpose of this paper is to consider the relative economic position of U.S. children and elderly as compared to identical dependent groups in nine other modem industrialized countries. In so doing, we find that some countries are willing to tolerate more inequality among dependents than are other countries.